Analisis Perubahan Tutupan Lahan Di Ekosistem Mangrove Kecamatan Lembar Kabupaten Lombok Barat - Rahman, Andi; Hayati, Hayati; Sjah, Taslim (LPPM Universitas Mataram, 2025)
West Lombok Regency. Using the Vector Geoprocessing method, the study processes and analyzes spatial GIS data, focusing on graphical data (geometry) and attributes (identity) through ArcMap Desktop. The main analysis techniques used include overlay analysis and buffer analysis, which are very important for spatial data analysis in GIS. This study uses mangrove distribution data from 1996-2021 which is analyzed to obtain the distribution of mangroves in the desired area. In Lembar District, there are four villages that have mangrove ecosystems, namely Eyat Mayang, Labuan Tereng, Lembar & South Lembar villages. In each village from year to year there is a change in area. The mangrove ecosystem in Lembar District from year to year has experienced an overall reduction starting from 1996-2021, experiencing a decrease of approximately 69%, namely from an area of 186 Ha to 59 Ha. However, there is one village that experienced an increase in mangrove ecosystems in 2016-2021, namely an increase of approximately 3 Ha. This cannot be separated from internal and external factors that occur so that they have an impact on changes in the mangrove ecosystem in an area. The factor that most influences changes in the area of mangroves is the existence of development in the area so that it has an impact on the mangrove ecosystem.